Challenges and solutions when applying implicit motor learning theory in a high performance sport environment: Examples from rugby league - Gabbett, T.; Masters, M. (International Journal of Sports Science and Coaching, 2011)
Skills that are learnt implicitly (i.e., without the accumulation of task-related rules and knowledge) have been shown to result in performance that displays stability in conditions of psychological stress, fatigue, multi-tasking, and over prolonged periods of time. Despite the wealth of evidence supporting the use of implicit motor learning strategies, the majority of this evidence has been generated from studies of novice performers rather than of experts. The aim of this paper is to describe some of the challenges faced by high-performance coaches and athletes who may wish to use implicit motor learning and to frame potential solutions with respect to the elite Australian National Rugby League competition. Practical training activities and techniques (e.g., errorless learning, random practice, cues, dual-tasking, and analogies), designed to facilitate the development of implicit skills that transfer robustly to high-performance competition environments, are presented.